Validity and reliability of the Thai version of the ASCRS SPEED II preoperative OSD questionnaire in Thai cataract surgery candidates. - Kaevalin Lekhanont; Paphada Ariyanonthacha; Chathaya Wongrathanandha; Prae Phimpho; Nontawat Cheewaruangroj (PLoS ONE)
Objectives To develop a Thai version of the American Society of Cataract and Refractive Surgery (ASCRS)-modified Standard Patient Evaluation of Eye Dryness (SPEED) II© preoperative ocular surface disease (OSD) questionnaire (ASCRS SPEED II-Thai) and evaluate its validity and reliability in Thai cataract surgery candidates. Methods The original English version of the questionnaire was translated and adapted cross-culturally to Thai language. The ASCRS SPEED II-Thai was evaluated for content validity, internal consistency, and test-retest reliability. Five experts in the ocular surface field critically reviewed the ASCRS SPEED II-Thai to measure the content validity indexes (CVI). A total of 105 cataract surgery candidates were recruited from an ophthalmology clinic to complete the questionnaire. Cronbach's alpha and intraclass correlation coefficient (ICC) were calculated to assess internal consistency and test-retest reliability, respectively. Results During the translation and cross-cultural adaptation processes, only two minor modifications were made to the original version for clarification without changing their meaning. All items in the ASCRS SPEED II-Thai had an item-level CVI of 1.00, representing complete agreement among content experts. The scale-level CVI was 1.00, indicating excellent content validity of the questionnaire. The participants found no difficulty in understanding each question in the pilot test. Cronbach's alpha for the ASCRS SPEED II-Thai was 0.82, indicating good internal consistency. The test-retest reliability was good to excellent, with ICC values ranging from 0.83 to 1.00 (P < 0.001). Conclusions The ASCRS SPEED II-Thai is a valid clinical tool with adequate reliability for preoperative OSD screening among Thai cataract surgery candidates.